Virulence Characteristics and Emerging Therapies for Biofilm-Forming Acinetobacter baumannii: A Review - Karma G. Dolma; Rachana Khati; Alok K. Paul; Mohammed Rahmatullah; Maria de Lourdes Pereira; Polrat Wilairatana; Bidita Khandelwal; Chamma Gupta; Deepan Gautam; Madhu Gupta; Ramesh K. Goyal; Christophe Wiart; et al. (Biology, 2022)
Acinetobacter species is one of the most prevailing nosocomial pathogens with a potent ability to develop antimicrobial resistance. It commonly causes infections where there is a prolonged utilization of medical devices such as CSF shunts, catheters, endotracheal tubes, and similar. There are several strains of Acinetobacter (A) species (spp), among which the majority are pathogenic to humans, but A. baumannii are entirely resistant to several clinically available antibiotics. The crucial mechanism that renders them a multidrug-resistant strain is their potent ability to synthesize biofilms. Biofilms provide ample opportunity for the microorganisms to withstand the harsh environment and further cause chronic infections. Several studies have enumerated multiple physiological and virulence factors responsible for the production and maintenance of biofilms. To further enhance our understanding of this pathogen, in this review, we discuss its taxonomy, pathogenesis, current treatment options, global resistance rates, mechanisms of its resistance against various groups of antimicrobials, and future therapeutics.